Pandemic COVID-19. Prevention Measures in the Russian Federation - N. I. Briko; I. N. Kagramanyan; V. V. Nikiforov; T. G. Suranova; O. Р. Chernyavskaya; N. A. Polezhaeva (Эпидемиология и вакцинопрофилактика, 2020)
Relevance. Humanity has been confronted with the global spread of dangerous viral diseases for centuries. Today a new coronavirus, SARSCoV-2, has been added to the list of potentially pandemic pathogens.The purpose of the article is to highlight, as much as possible, the physical and chemical properties of coronavirus, its epidemiology, framework for the disease prevention and treatment in various population groups and healthcare workers. The article provides a list of regulatory documents, a detailed guidance for healthcare professionals on how to act in case of identifying a patient with suspected COVID-19 in healthcare facilities, and a description of the coronavirus disease outbreak situation in the world and in the Russian Federation.Conclusions. The sanitary protection of the territories of the countries represents the main way to shield a population from a dangerous infectious disease. Therefore, the collaboration of physicians from all over the world and constant exchange of information among them is of crucial importance. The COVID-19 pandemic requires decisive, coordinated, global quarantine measures; biological protection of the population, collaboration on the vaccine’s development and treatment methods, and joining efforts against the panic and misinformation.